Revisiting the Role of Institutional Ownership in Sharia-Compliant Stock Performance: Evidence from the Jakarta Islamic Index (2020–2023) - Taufik, M. Iman; Dwiastuti, Ninuk; Lala, Lala (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study examines the effect of institutional ownership on the performance of Sharia-compliant stocks listed on the Jakarta Islamic Index (JII) during the period 2020–2023. Using a quantitative research approach with an ex post facto design, this study analyzes secondary data from 16 companies that consistently appeared in the JII for four consecutive years. The stock performance was measured using annual log-returns, while institutional ownership was calculated as the percentage of shares held by institutional investors. The data were analyzed using simple linear regression after fulfilling classical assumption tests, including normality, linearity, and heteroscedasticity tests. The results show that institutional ownership has a negative but statistically insignificant effect on Sharia stock returns, explaining only 3.4% of the variation. These findings imply that institutional ownership is not a dominant factor influencing the performance of Sharia stocks in Indonesia, particularly during periods of market volatility. Instead, factors such as Sharia governance quality, ethical compliance, and sector-specific risks may play a more important role. This study contributes to the literature on Islamic capital markets by offering empirical evidence that conventional ownership-performance models may have limited applicability in Sharia contexts and encourages future research to consider alternative explanatory variables grounded in Islamic principles